Analysis of otorhinolaryngology related surgeries performed in a tertiary care center over four years’ period - Koirala, Krishna Prasad (Asian Journal of Medical Sciences, 2020)
Background: The trend of ENT related surgeries worldwide have changed over the years due to better understanding of the disease process, patient awareness, surgical workshops, conferences, etc. Many ENT related hospitals and subspecialty centers of surgical excellence have been established in different parts of our country in recent years. There have been substantial patient preferences to specialty than general hospitals. Aims and Objectives: The current study was designed to compare different surgeries performed during the four years period from 2015 to 2018 and observe the changing trends in common surgeries during these years. Materials and Methods: This is a prospective study carried out in the Department of ENT- HNS, Manipal Teaching Hospital, Pokhara, Nepal from 1st Jan 2015 to 31st Dec 2018. Patients of all age and both sex operated under the department of ENT were included in the study. Data wereanalysed and results were published to look for the changing trends of different types of surgeries. Results: Out of 945 surgeries performed during these 4 years, major surgeries were rigid esophagoscopy, septoplasty, myringoplasty, mastoid exploration, tonsillectomy and endoscopic sinus surgery. Commonly performed intermediate and minor surgery was excision of minor and intermediate head and neck lesions. Excision was in the rise, esophagoscopy and myringoplasty were almost constant and septoplasty and modified radical mastoidectomy were in the decreasing trend (p<0.05). Conclusion: In our study, the trend of performing major otolaryngology and head and neck surgeries in our institution is in the descending trends in the recent years after 2015.Common ENT related surgeries shall be in the descending trend while specialty services will be ever progressing in the future.